Euregionale 3 : Plan : Gids. - van Grevenstein, Alexander; Himmelreich, Ad; Kenis, Jan (Maastricht : Bonnefantenmuseum, 1988)
Bleus, Guy ; Caris, Gerard ; Garcet, Robert ; Brand, Weber ; Klinikum
Euregionale 3, Dominicanenkerk, Maastricht, 5 - 27.XI.1988
boek